Electrical pole climbing robot: for wiring and repairing distribution lines - Khalid, Zahra Bakhtiar; Ullah, Md. Hasib; Ahmed, Razu; Choudhury, Zakir Hasan; Kaish, Imrul; Rhaman, Md. Khalilur (© 2016 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 18th International Conference on Computer and Information Technology, ICCIT 2015; Military Institute of Science and Technology (MIST)Mirpur CantonmentDhaka; Bangladesh; 21 December 2015 through 23 December 2015 [© 2015 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICCITechn.2015.7488098